Between Past and Future - 1/23
Contains the second part of Prof. Ilya Prizel’s speech in the last panel of the “Between Past and Future: The Revolutions of 1989 and the Struggle for Democracy in Central and Eastern Europe" international conference held at CEU in March 1999. Ilya Prizel’s presentation is followed by Jeffrey Wasserstrom, Professor of History at the University of California and Polish Historian and Professor Irena Grudzińska Gross. Chairman of the panel is CEU Prof. Alfred Rieber.